Das Verbot von extremistischen Organisationen im schweizerischen Recht Verfassungsrechtliche Voraussetzungen und Rechtsgrundlagen - Fellmann, Jeremias (sui generis Verlag, 2023)
Bans on organizations are not part of the traditional range of instruments used in dealing with extremist phenomena in the Swiss legal system. In recent years, however, there has been a paradigm shift in this regard, especially since there has been a general, abstract basis for a ban on extremist organizations in individual cases for the first time since September 1, 2017. This thesis is devoted to the question of the conditions under which a ban on extremist organizations is permissible from a constitutional point of view. To this end, the author examines whether and to what extent extremist efforts enjoy protection under fundamental rights. He also examines the existing legal bases for bans on organisations, specifically Article 74 of the Intelligence Service Act (NDG), for their conformity with the constitution.